PENGARUH PENGETAHUAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR KABUPATEN SRAGEN - Marlina, Iin; Suharno, Suharno; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
Taxes are a source of state revenue in increasing development interestsand one of the sources of development financing in the welfare of society. Thepurpose of this study was to determine (1) The effect of taxpayer knowledge onmotor vehicle taxpayer compliance, (2) The effect of tax penalties on motorvehicle taxpayer compliance. The research method uses a survey method using aquestionnaire, the type of data used is quantitative data, the data source used isprimary data and secondary data. The population in this study were all motorvehicle taxpayers registered at the SAMSAT Office in Sragen Regency until 2019as many as 522,344 people. The sampling technique used convenience sampling,namely a number of 100 respondents, the data collection methods used:questionnaires and documentation. The data analysis technique used isdescriptive analysis, validity test, reliability test, classical assumption test,multiple linear analysis, t test, F test and coefficient of determination.The result of t count 2.962 with a p-value of 0.004 < 0.05, so Ho isaccepted, meaning that there is a significant effect of taxpayer knowledge (X1) onmotor vehicle taxpayer compliance (Y). The result of t count -1.411 with a p-valueof 0.162 > 0.05 means that Ho is accepted, meaning that there is no significanteffect of tax sanctions (X2) on motor vehicle taxpayer compliance (Y). Thedetermination test shows an Adjusted R Square value of 0.090. It can beconcluded that the motor vehicle taxpayer's frustration variable can be explainedby the two independent variables, namely taxpayer knowledge and tax penaltiesfor other causes outside the model.